2019
DOI: 10.1166/jnn.2019.17025
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Online Learning With Multiple Postsynaptic Neurons Based on Spike-Timing-Dependent Plasticity Using a Thin-Film Transistor-Type NOR Flash Memory Array

Abstract: We present a two-layer fully connected neuromorphic system based on a thin-film transistor (TFT)-type NOR flash memory array with multiple postsynaptic (POST) neurons. Unsupervised online learning by spike-timing-dependent plasticity (STDP) on the binary MNIST handwritten datasets is implemented, and its recognition result is determined by measuring firing rate of POST neurons. Using a proposed learning scheme, we investigate the impact of the number of POST neurons in terms of recognition rate. In this neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Oxidative stress can induce apoptosis [20], and the apoptosis may result in the loss of postsynaptic proteins [21]. Postsynaptic current was modulated by postsynaptic proteins [22] while postsynaptic neurons modulate learning [23] and their dysfunction will impair memory [24]. Thus, oxidative stress can impair learning and memory by affecting postsynaptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress can induce apoptosis [20], and the apoptosis may result in the loss of postsynaptic proteins [21]. Postsynaptic current was modulated by postsynaptic proteins [22] while postsynaptic neurons modulate learning [23] and their dysfunction will impair memory [24]. Thus, oxidative stress can impair learning and memory by affecting postsynaptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…To keep the average threshold voltage of all output neurons, the threshold voltage of neurons which are not fired are lowered by (10/output neuron number) mV. Adaptive neuron threshold is effective in improving the performance of the network by preventing the exclusive or dormant firing of certain neurons [23,24]. A number of previous works were reported to compose CMOS-compatible neuron circuits enabling these various functionalities [25,26], suggesting the possibility of being effectively combined with our synaptic array as shown in figure 5(c).…”
Section: Device Structures and Measurement Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Researchers incessantly have demonstrated that the more hardware-wisely implemented artificial neural networks (ANNs) are quite successful in tasks related to image pattern recognition. [7][8][9][10] In the development of the ANN hardware, two-terminal electron devices have gained interest due to their geometrical analogy with the biological synapses. [11][12][13][14][15][16][17][18] In this work, resistive-switching random-access memory (RRAM) with high scalability and operation speed is used for a hardware-driven ANN.…”
mentioning
confidence: 99%